41st Annual Convention of the National American Woman Suffrage Association - University of Washington Libraries. Special Collections Division (1909)
Printed on cover: Pymouth Church, Seattle, Washington, July 1 to 6, 1909."Woman Suffrage Day" at the A.Y.P. Exposition, Wednesday July 7. Lists general officers and committees, program for the convention and activities for July 7th "Woman Suffrage Day at the Alaska Yukon Pacific Exposiition".